Effect of nanoparticle shape on natural convection in hybrid nanofluid inside square cavity - Mohd Ali Hanafiah, M. A.; Ab Ghani, A.; Hafidzuddin, M. E. H.; Md Arifin, N.; Mohamad Som, M. N. (Lviv Polytechnic National University, 2024)
A numerical study of natural convection in a square cavity with Al2O3-Cu/water hybrid nanofluid, focusing on the effects of nanoparticle shape, is conducted. The governing partial differential equations and corresponding boundary conditions are transformed into nondimensional forms and solved using the finite element method. The flow and heat transfer characteristics are graphically illustrated and explained for different nanoparticle volume fractions and shapes, with corresponding average Nusselt numbers. It has been observed that a variety of nanoparticle shapes effect, as the empirical nanoparticle shape factor m increases, the total surface area of the nanoparticle increases. This causes more heat can be dissipated and in turn, produces a higher heat transfer rate.